Out of hours workload of a suburban general practice: deprivation or expectation. - Pitts, J (1990)
The out of hours workload of a training practice in a suburban and semirural area on the south coast of England was studied for one year. An overall rate of contact of 273/1000 patients was found, which indicated a workload greater than that reported in most other studies. The duty doctor received over 35 telephone calls from patients during some Saturdays (1200 Saturday to 0800 Sunday) and Sundays (0800 to 0800 Monday), up to five being between 2300 and 0700. Of the patients who contacted a general practitioner, 44% were given advice by telephone and 4.9% were admitted to hospital. The admission rate was lower than that given in other studies. A considerable proportion of the workload arose from doctors covering the casualty department of a cottage hospital. Patients having a high expectation of 24 hour care by general practitioners in an area of comparative affluence (Jarman indices -13.8 to 1.7) may account for this aspect of the workload.